Diotima's eudaemonism: intrinsic value and rational motivation in Plato's Symposium - Wedgwood, R (Brill, 2009)
This paper gives a new interpretation of the central section of Plato's Symposium (199d-212a). According to this interpretation, the term "καλόν", as used by Plato here, stands for what many contemporary philosophers call "intrinsic values"; and "love" (̓έρως) is in effect rational motivation, which for Plato consists in the desire to "possess" intrinsically valuable things - that is, according to Plato, to be happy - for as long as possible. An explanation is given of why Plato believes that "possessing" intrinsically valuable things, at least for mortals like us, consists in actively creating instatiations of the intrinsic values, both in oneself and in the external world, and in knowing and loving these intrinsic values and their instantiations. Finally, it is argued that this interpretation reveals that Plato's "eudaemonism" is a different and more defensible doctrine than many commentators believe.